Reinforcement of the Antioxidative Properties of Chickpea Beverages Through Fermentation Carried Out by Probiotic Strain Lactobacillus plantarum 299v - Skrzypczak, Katarzyna; Jabłońska- Ryś, Ewa; Gustaw, Klaudia; Sławińska, Aneta; Waśko, Adam; Radzki, Wojciech; Michalak-Majewska, Monika; Gustaw, Waldemar (Journal of pure & applied microbiology : an international research journal of microbiology, 2019)
The purpose of the research was to obtain different variants of chickpea beverages and subject them to probiotic fermentation carried out by Lactobacillus plantarum 299v in order to compare properties of received products. The study focused on the influence of the fermentation process on changes in protein profiles, antioxidative properties, pH values, and reducing power (RP). The analyzed variants of chickpea beverages exhibited diversity in terms of RP. Fermented products were characterized by significantly higher values of RP (A700) ranging from 0.1 to 0.29 than unfermented ones (value in range from 0.04 to 0.09). Whereas, pH values of fermented products were lower (from 4.46 to 5.64) to than unfermented beverages (6.68 to 7.57). The results indicate also the presence of β-conglycinin and glycinin (which are considered as one of food allergens) in analyzed chickpea-based beverages, however the probiotic fermentation contributed to strong hydrolysis of those components. Among tested variants of the chickpea products, the beverages with vanillin sugar and coconut flakes (unfermented as well as fermented) received the highest notes of general consumer acceptance in preliminary sensory assessment. The fermentation of the chickpea beverages with the probiotic strain significantly increased the reducing power of the products, revealed antioxidative-enhancing properties and contributed to hydrolysis of β-conglycinin (7S) and glycinin (11S) fractions.